International Experience in Attracting Foreign Direct Investment - B.Ruzmetov; Z.K. Jumaeva; M.Xudayarova (Research Parks Publishers, 2021)
The article substantiates the need for an effective policy of attracting foreign direct investment, identifies external and internal factors influencing the ability and volumes of attracting foreign investment in the economy. Based on studying the global experience in attracting foreign investments, the main directions for increasing the investment attractiveness of the economy have been identified